1998
DOI: 10.1046/j.1365-3156.1998.00176.x
|View full text |Cite
|
Sign up to set email alerts
|

Recurrence of kala‐azar after PKDL: role of co‐factors

Abstract: SummaryRecurrence of kala-azar after post kala-azar dermal leishmaniasis (PKDL) has remained uncommon. We report here two patients with recurrence of kala-azar (KA) after development of PKDL. In one case the second attack of KA was preceded by repeated attacks of malaria and tuberculosis, and in the other the recurrence of KA followed an attack of measles. While measles has earlier been suggested as co-factor in inducing transformation from sub-clinical to clinical kala-azar, malaria was demonstrated to enhanc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2000
2000
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 4 publications
0
10
0
Order By: Relevance
“…However, the proportion of PKDL relapse following a 3mo PKDL treatment with miltefosine was significantly higher (43%) compared to PKDL patients treated with 4mo of miltefosine [ 121 ]. There were two case reports of recurrence of VL following PKDL possibly triggered by immunosuppression due to concurrent infection [ 123 ]. A higher proportion of macrophages infected with the parasite was reported in relapse.…”
Section: Resultsmentioning
confidence: 99%
“…However, the proportion of PKDL relapse following a 3mo PKDL treatment with miltefosine was significantly higher (43%) compared to PKDL patients treated with 4mo of miltefosine [ 121 ]. There were two case reports of recurrence of VL following PKDL possibly triggered by immunosuppression due to concurrent infection [ 123 ]. A higher proportion of macrophages infected with the parasite was reported in relapse.…”
Section: Resultsmentioning
confidence: 99%
“…Nandy et.al study has shown that active cases of VL develop after successful treatment of PKDL. 5 In Sudan PKDL heals spontaneously and does not need treatment except in chronic cases of more than 6 months to one year duration. In India patients need treatment, as PKDL serves as reservoir for VL.…”
Section: Introductionmentioning
confidence: 99%
“…Those who made the earliest reports of VL after PKDL (Brahmachari, 1928;Napier and Das Gupta, 1930;Sen Gupta, 1968) made no attempts to identify the event(s) that may have triggered the second attack of VL (in an era when HIV was unknown). In the two cases described by Nandy et al (1998), however, measles or pulmonary TB preceded the visceral recurrence and may have led to immunosuppression.…”
Section: Impact Of a Co-factor On The Dynamics Of Leishmania Donovanimentioning
confidence: 92%
“…VL during or after PKDL is, in fact, an extremely rare phenomenon in India. Except for Nandy et al (1998), those who reported Indian patients in which the visceral disease has recurred after PKDL (Brahmachari, 1928;Napier and Das Gupta, 1930;Sen Gupta, 1968) appear to have made little attempt to understand the possible mechanism(s) involved in the recurrence. Surprisingly little is known, however, about the nature and extent of the immune response that usually provides life-long protection against the recurrence of VL.…”
Section: Impact Of a Co-factor On The Dynamics Of Leishmania Donovanimentioning
confidence: 99%